Quality of life of hemodialysis patients in selected teaching hospitals of Chitwan - Ghimire, Srijana; Lopchan, Milan (Journal of Chitwan Medical College, 2017)
The quality of life (QOL) needs to be regularly assessed in hemodialysis patients. Hemodialysis patients suffer from average quality of life and survival. A descriptive research design was used, 96 respondents who had received haemodialysis treatment after completion of 1 month duration of hemodialysis in two different teaching hospital at Bharatpur, Chitwan. Data was collected by using standard tool Short Form-36 version2 through face to face structure interview schedule. The objective of study is to find out the quality of life (QOL) of haemodialysis patients. Various test such as one sample t-test, ANOVA test, independent t-test, Kruskal-Wallis test and Mann-Whittney U test, Pearson’s correlation was applied. The findings showed that higher proportion of respondents were from 40-59 years (41.0%) and male (62.2%). The mean±SD was 57.45±16.25, 55.72±22.41 and 60.04±11.50 in overall QOL, physical and mental component summary respectively which was slightly above the average. All dimention and sub scale was satistically significant. Younger respondents had statistically significant with overall QOL (p